Drones and the law : international responses to rapid drone proliferation - Sehrawat, Vivek (Emerald Publishing Limited, 2020)
The growing ubiquity of drones means that they are more readily available for both terrorists and civilians to use. At the same time, the military use of drones has globalised. Yet regulations for their international use, both military and domestic, are sparse and lacking in clarity, and most books on the legality of drones tend to be written by journalists or activists. Drones and the Law: International Responses to Rapid Drone Proliferation presents a fresh, scholarly perspective on the increasingly complex relations between drone usage and international and privacy law. Combining expert insights into strategy, international law, international humanitarian law, targeted killing, ethics, and privacy, Vivek Sehrawat offers an important historical and context for understanding how drone usage has become widespread; investigates how international law and international humanitarian law on the use of force interact with the rapid proliferation of military drones; and outlines how civilian use of drones poses specific challenges to national privacy laws in large countries such as the UK, the USA, and India. Throughout, Sehrawat discusses potential world policies for drone strikes and counter terrorism and debunks myths about current drone capabilities and the law regarding drone usage, making this book a useful and timely addition to the growing literature on drones and the law. For its rigorous legal research that offers a precise, accurate, and authoritative account of the legal challenges posed by rapid drone proliferation, Drones and the Law is a must-read for students and scholars of law and international relations.
Includes index.
Keywords: Drone aircraft -- Law and legislation.; Privacy, Right of.; Law, Privacy.; Public international law.; elektronické knihy; electronic books